Measurement of The Physiological Condition of Cricket National Athlete - Tangkudung, Albert Wolter Aridan; Nurdin, Fatah; Yuliasih, Yuliasih; Juniarto, Mastri; Diyananda, Dzulfiqar (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
This study aims to determine the physiological condition of Cricket national athletes. The method used in this study is the quantitative descriptive method. The population in this study is national cricket athletes totaling 30 people consisting of 15 women and 15 men. The sampling technique with the total sampling technique is that all members of the population are sampled, which is as many as 30 people. This research was conducted at the Jakarta cricket field with measurements of the physiological condition of athletes. The results of the study on male athletes showed the average results of measuring the physical fitness component of flexibility with a V-sit and reach test of 33cm, balance of 28 seconds, speed of 20meter which is 3 seconds, agility with shuttle run 5x8 which is 11 seconds, MBT 4.8 meters; THJ 6 meters, 1 minute push up 52 times, 2-minute sit ups 76 times, 1-minute squat 57 times, core 12 level 11 and cardiopulmonary endurance with bleep test get VO2Max of 44 ml. kg/minute. The female athletes showed the average result of measuring the physical fitness component of flexibility with the V-sit and reach test of 31.1cm; balance of 19.4 seconds; the speed of 20 meters is 3.6 seconds; agility with a 5x8 shuttle run of 13.7 seconds; 0meter MBT (for female athletes do not take the MBT test); THJ is 4.9meter; 1-minute push up 31.7 times; 2-minute sit-ups 61.7 times; 1-minute squats 45.3 times; core 12 level 11 and cardiopulmonary endurance with bleep test get VO2Max of 41.3 ml. kg/minute. So it can be concluded that from the average test results of the draining of physiological conditions of cricket national athletes are included in the good category. If displayed in the average performance, male athletes have 87.59% performance and female athletes have 86.40% performance.